The Long-run Money Demand Function: Empirical Evidence from Italy - Dritsaki, Chaido; Dritsaki, Melina (International Journal of Economics and Financial Issues, 2019)
The stability of money demand is fundamental in ensuring a county’s effective monetary policy and it is being threatened when major shocks are taking place. The current paper aims to examine the factors that influence money demand in Italy for the period 1960-2017. Auto Regressive Distributed Lags (ARDL) technique and Error correction model (ECM) were applied to test for long-run and short-run coefficients respectively, while cumulative sum of recursive residuals stability test (CUSUM) evaluated parameters’ stability. The results show that there is both a long- run and short- run relationship among the variables used. Real income, long run interest rate and inflation comply with the expectations of monetary theory. Furthermore, the stability tests and unit circle confirm the long- run relationship among variables. Finally, the stability condition is satisfied when money demand for Italy is estimated using the demand for narrow money (M1) for the examined period. Keywords: Money demand stability, ARDL model, Vector Error Correction Model, stability of the coefficients, Monetary aggregates, Italy JEL Classifications: E41, E52, C22 DOI: https://doi.org/10.32479/ijefi.8943